HPLC and UV-spectrophotometry analysis of flavonoids in spray-dried and freez-dried extracts of Teucrium polium L. (Lamiaceae) - Gjoshe Stefkov; Marija Karapandzova; Marina Stefova; Vassya Bankova; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
Тhe aim of the study was identification and determination of the content of flavonoids in dry extracts of Teucrium polium, collected from Republic of Macedonia. Two different drying procedures were used, freeze and spray draying. In freeze-dried (FDE) and spray-dried (SDE) extracts of aerial parts of T. polium five flavone aglycones (luteolin, apigenin, cirsiliol, cirsimaritin and cirsilineol) were identified by HPLC method, on the base of retention times and UV spectral data of the components of the extracts in comparison to the authentic samples of flavonoids. Additionally, seven glycosides of apigenin and luteolin were tentatively identified. No significant differences in the composition nor in the content of identified flavonoids were found between both extracts. The content of total flavonoids determined by UV-spectrophotometry with AlCl3 was 72.8 ± 0.62 mg Lut/g and 73.34 ± 0.53 mg Lut/g in FDE and SDE extract of T. polium, respectively.